Contributions of visual management to trend analysis (ModaPalavra e-periódico, 2021)
This text, an integral fragment of the ongoing master's research, has as main theme the theoretical-conceptual approach between trends and visual management, aiming to qualify the trend analysis method proposed by Dragt (2017) from principles and tools of visual management . In methodological terms, the article is designed in the moments of conceptualizing important terms through the Bibliographic Review, as well as the collection, reduction, categorization and interpretation of data via Qualitative Data Analysis. Furthermore, the text is classified as being of a basic, qualitative nature and with descriptive objectives. The results achieved demonstrate that the principles and tools of visual management add different advantages to the process, such as innovation, agility and encouraging the collaboration of the participants of those involved in the analysis of trends.
Keywords: trend analysis; visual management; literature review